Pendekatan Holistik dalam Trauma Healing Berbasis Kuis Edukatif Risiko Penyakit pada Masyarakat Terdampak Tanah Bergerak - Theodora Rosaria Geglorian; Ita Nur Itsna; Uswatun Insani; Ani Ratnaningsih; Maelia Unayah; Arriani Indrastuti; Arifin Dwi Atmaja; Woro Hapsari; Devva Saptia Maharani; Anggun Tiara Suci (Jurnal Informasi Pengabdian Masyarakat, 2026)
The land movement disasters can cause physical and psychological problems among affected communities, such as anxiety, stress, and fear. These conditions require a holistic nursing approach through trauma healing and health education. This community service activity aimed to improve community understanding regarding post-disaster disease risks while supporting the psychological recovery of the community in Padasari Village, Tegal Regency.The method used was supportive group therapy through educational games in the form of Disease Risk card quizzes containing Clean and Healthy Living Behavior (PHBS) materials and post-disaster disease risks. The activity involved 20 adults and elderly people affected by land movement disasters.The results showed that participants were enthusiastic, actively interacted, and more easily understood health materials through educational game media. In addition, the activity helped create a relaxed atmosphere and increased community social support. The holistic nursing approach through the Disease Risk educational quiz can serve as a promotive and preventive effort in supporting the physical and psychological recovery of disaster-affected communities. Therefore holistic nursing-based trauma healing through Disease Risk educational quizzes among communities affected by land movement disasters in Padasari Village, Tegal Regency, was able to improve social interaction, health understanding, and support the psychological recovery of the community through an interactive and enjoyable educational atmosphere.